The Role of External Signs of Multi-volume Editions in the Reconstruction of Kolyvan-Voskresensky Mining Plants Book Collection - T. N. Ilyushechkina (Библиосфера)
The purpose of the article is to determinate the role of the external signs in the multi-volume editions in the book marking and to solve the practical problems of reconstruction of the original composition of the book collection of Kolyvan-Voskresensky mining plants (KVMP) for the period of the XVIIIth – early XIXth centuries. This topic is considered in continuation of such issues as the reconstruction of KVMP book collection, which has already attracted the attention of our predecessors, such as formation of the fund, its cataloguing, redistribution among official Altai libraries and others. For the first time one speaks not on mechanical fixation of certain features of the copies, but on the study of these characteristics “interaction mechanisms” under the conditions of redistribution of preserved copies among different Siberian repositories. The focus is only on the signs of the early period of the existence of the book collection: stamp imprints, textual and numerical service records, specific features of bindings etc. The emphasis on early signs is due to an appeal to the earliest accounting document – “Inventory of books of Barnaul State Library, compiled by P. K. Frolov” (1809). This makes it possible to show in detail the connection between the signs on the books and the articles corresponding to these books official document and to determine the original composition of different multi-volume editions or, on the contrary avoid combining volumes that do not correspond to each other into one set. The structure of the article is determined by analysis of numerous details associated with each copy from three state repositories: State Public Scientific Technological Library of the Siberian branch of Russian Academy of Sciences, Novosibirsk State Regional Scientific Library, Research Library of Tomsk State University. The main object of the study is records of “ordinary” and “private” copy numbers, official numerical records, handwritten evidences on the inclusion of numerous drawings in book blocks as an integral part of these editions, different styles of crossing out typographical letters with ferrous ink and other signs. The features of stamp imprints are taken into account. In some cases the paramount importance of the binding characteristics is shown. The role of external signs in combining disparate copies as sets of multi-volume editions is recognized as leading. It is concluded that not just recording, but rather a thorough study of the external features of the extant sets and odd volumes of multi-volume editions is one of the basic conditions for the successful reconstruction of the book collection of KVMP.